PEDAGOGICAL INNOVATION WITH AUGMENTED REALITY IN FOLK POETRY EDUCATION: A TOOL FOR RECONSTRUCTING LOCAL WISDOM THROUGH IMMERSIVE LEARNING - Yosi Wulandari; M Ardi Kurniawan; Denik Wirawati; Hari Adi Rahmad (LLDIKTI Wilayah X, 2026)
This study presents a systematic literature review (SLR) on the integration of augmented reality (AR) in folk poetry education from 2019 to 2024. Although AR is increasingly prominent in STEM fields, its application in the humanities, especially literary instruction and cultural heritage preservation, remains limited. As an oral and symbolic form of intangible heritage, folk poetry presents pedagogical challenges related to abstraction, generational gaps, and cultural disconnection. Using the PRISMA framework, 94 Scopus-indexed publications were screened, resulting in 16 peer-reviewed articles for full analysis, focusing on trends, pedagogical strategies, and cultural dimensions of AR-based poetry learning. Findings indicate that AR enhances comprehension of symbolic language, fosters cultural empathy, and promotes multisensory learning through interactive visualisations, while revitalising oral traditions by linking digital technologies with traditional narratives. However, challenges persist, including limited infrastructure, insufficient teacher readiness, and the lack of culturally adaptive AR content. These results suggest future research integrating adaptive technologies, cultural sensitivity, and ethical considerations. Developing affordable, locally relevant AR tools has the potential to transform folk poetry instruction, particularly in Indonesia’s Kurikulum Merdeka, by aligning cultural preservation with innovative pedagogy and 21st-century competencies.